A dog needs a bone! - Wood, Audrey (New York : Scholastic, 2008)
In this rhyming tale, a dog makes extravagant promises to its mistress if only she will give it a bone.
1.8
K-3.
K-3
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Stories in rhyme; Dogs -- Fiction; Stories in rhyme